Sensitivity of harmonic load model parameters to voltage and current waveforms - Milanovic, Jovica; Gul, O.; Milanović, J. V. (IEEE, 2002)
A generic load model for harmonic loads is used in the study. The model consists of resistance, inductance and capacitance connected in parallel with a current source. The modelling technique is based on using actual recorded data and it is particularly suitable for developing aggregate load models. The study concentrates on establishing the sensitivity of the load parameters (i.e., R, L and C) to variation in measured voltage and current waveforms. In an attempt to establish the ranges of variation of different parameters various test cases are used including several sets of actual field measurements.